A survey of public bookmobile services in Luzon - Baker, Elaine C. (1978)
This study is a survey of the six bookmobiles which provide public service now operating in Luzon: the Tarlac bookmobile, the privately-owned bookmobile sponsored by the Social Communications Center and S.C. Johnson and Son, Inc., the Makati bookmobile, the Batangas bookmobile, the jointly-sponsored Learning Mobile which takes films and books to schools in Baguio City and Benguet Province, and the Quezon bookmobile.